The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/ece3.1926
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high proportions of male flowers and geographic variation in floral ratios within male figs of Ficus tikoua despite pollinators displaying active pollen collection

Abstract: Most plants are pollinated passively, but active pollination has evolved among insects that depend on ovule fertilization for larval development. Anther‐to‐ovule ratios (A/O ratios, a coarse indicator of pollen‐to‐ovule ratios) are strong indicators of pollination mode in fig trees and are consistent within most species. However, unusually high values and high variation of A/O ratios (0.096–10.0) were detected among male plants from 41 natural populations of Ficus tikoua in China. Higher proportions of male (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Mature figs containing fig wasp adult offspring were removed and placed separately in fine‐mesh bags to let wasps emerge naturally. The figs were then cut in half and the distribution patterns of their male flowers were recorded as either ostiolar, scattered or intermediate (Deng et al, ). The fig wasps that emerged from the figs were stored in ethanol at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mature figs containing fig wasp adult offspring were removed and placed separately in fine‐mesh bags to let wasps emerge naturally. The figs were then cut in half and the distribution patterns of their male flowers were recorded as either ostiolar, scattered or intermediate (Deng et al, ). The fig wasps that emerged from the figs were stored in ethanol at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Within its large genus, F. tikoua is exceptional in terms of the variation it exhibits in inflorescence composition. Deng et al () identified three types of male flower distributions inside its male figs. They contain either small numbers of male flowers concentrated around the ostioles (ostiolar type) or larger numbers of flowers scattered throughout the figs (scattered type).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations